Social Criticism in the Text of Dharmasonya - Aryanto, Aris; Sudardi, Bani; Purwanto, Andrik; Wakit, Abdullah (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
This study took a closer look at the socio-condition of the Javanese people in Surakarta at the time this text was written through a perspective of critical-sociological studies. The data collection method was literature studies which aimed at analyzing several sources of old Javanese scripts, Serat Dharmasonya Serat Wedhatama, text of KGPAA Mangkunegara IV, Serat Tjemporet written by R. Ng. Ranggawarsito and some other studies on the life world of the Javanese palace in Surakarta 1830-1939 , the work of Soeratman Darsiti. Thus, the present text of the Dharmasonya was read through seeing the historical life of the Islamic religion. The main objective of this study was to probe the social system in which the Dharmasonya text was initially produced. The assumption laid on a reason that the social systems implemented by the Javanese community at the time were relatively different in each place. This study concluded that the Javanese community in Surakarta was divided into four levels, namely: kinghood, nobles, courtiers, common society. As a result of the influence of the European or colonial invasion to peoples lifestyles have had led to moral decadence and spiritual shallow in the community. This was because the feudalism and colonialism system committed by the local indigenous towards the Javanese community.